Analysis Of Financial Performance Measurement Based On Net Profit Margin, Return On Assets And Return On Equity In Companies Listed On The Indonesia Stock Exchange - Ramadhani, Laily (Jurnal Ekonomi, 2024)
Based on financial report data from PT. Ultrajaya Milk, Tbk. seen from the profitability ratio provides an overview of changes in financial position in each period, this shows that the company's profit fluctuates. For this reason, a more specific analysis is needed to get a clearer picture of the increase and decrease in company performance that occurs each year. So this research aims to assess the financial performance of PT.Ultrarajaya Milk,Tbk. During 2018-2022 based  on  Profitability Ratios consisting of Net Profit Margin, Return On Assets and Return On Equity. Based on the results of research and discussion, it can be concluded that PT.Ultrajaya Milk,Tbk. During 2018 to 2022, looking at the Profitability Ratio based  on Net Profit Margin, Return  On Assets and Return On Equity, it shows that financial performance results are considered less good, this is based on the results of calculations for 5 obtained an average net profit margin value of 15.98%, return on assets of 14.25% and return on equity of 19.52% years which are still far below the industry average standard.